Rancang Bangun Sistem Informasi Booking Wedding Organizer Berbasis Website di Keina Decoration - Tryana, Anjas; Fatah, Nugraha Nurul (Jurnal Accounting Information System (AIMS), 2025)
This study discusses the development of a web-based information system for booking wedding organizer services at Keina Decoration, a company engaged in engagement and wedding event decoration. The main problems faced by the company included limited digital visibility, unstructured service information, manual booking processes through messaging applications, and difficulties in building customer trust. To address these issues, a web-based system was designed using PHP with the Laravel framework, a MySQL database, and an interface supported by Bootstrap and JavaScript. The research employed a research and development approach with the Software Development Life Cycle (SDLC) model, consisting of requirement analysis, system design, development, testing, and evaluation. User requirements were documented for both customers and administrators, and black box testing was applied with specific evaluation criteria. Quantitative evaluation was conducted by comparing the manual and new systems, showing significant improvements: average booking time was reduced from 30 minutes to 5 minutes, booking errors decreased from 15% to 2%, and user satisfaction increased from 3.1 to 4.6 on a 5-point scale. The results indicate that the system not only improves operational efficiency and accuracy but also strengthens the professional image and competitiveness of Keina Decoration. The practical contribution of this research is providing a digital solution for wedding organizers to enhance customer experience and trust. The academic contribution lies in enriching the literature on information system implementation in the creative industry, which remains limited. Future development may integrate online payment gateways, automated notifications, and transaction analytics to support strategic decision-making.